Investigation of competitive tar reforming using activated char as catalyst. (February 2019) - Buentello-Montoya, David; Zhang, Xiaolei; Marques, Simão; Geron, Marco
Abstract: Syngas tar removal is one of the biggest challenges for the gasification of biomass as a clean energy source. Efforts to understand the reforming mechanism of tar compounds have been continuous during the last decades. Kinetic studies often employ a single tar species, neglecting possible interactions between different tar compounds. On the other hand, char, a by-product from biomass gasification, presents opportunities to catalyze tar reforming. In this work, reforming experiments were conducted in a fixed-bed reactor using syngas with a known mixture of benzene (C6 H6 ), toluene (C7 H8 ) and naphthalene (C10 H8 ). Hardwood char and an in-situ CO2 -activated hardwood char were used as catalysts. The activated hardwood char exhibited the best reforming capabilities by converting 44% and 90% of the tars at 750 and 850°C, respectively, compared to 24% and 87% tar conversion obtained with the regular hardwood char at 750 and 850°C, respectively. From the experiments, a reduced mechanism model was proposed. This mechanism was used in computational simulations for analysis of the reaction kinetics, including possible catalyst selectivity. It was found that under a range of conditions, the benzene degradation is slower than its formation rate from toluene and naphthalene decomposition. This leads to increases in the benzene fraction at temperatures around 700°C. If the naphthalene and toluene concentrations are sufficient, benzene will accumulate even at high temperatures (around 800°C) regardless of residence times. It can be concluded that when benzene, toluene and naphthalene are present together, char favors the heterogeneous reforming of toluene and naphthalene, with benzene following an homogeneous reforming pathway.